2012
DOI: 10.1111/j.1742-481x.2012.01011.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of negative pressure therapy and hyaluronic acid for the management of post‐traumatic lower limb injury

Abstract: Management of severe limb trauma continues to challenge surgeons. Suitable treatment should be individualised for each patient, taking into consideration not only the wound extremity but also the associated injuries, age and socioeconomic status of the patient with the goal to recover function and to improve patient quality of life. The aim of this report is to present a severe degloving multiplane lower limb injury case in which a conservative treatment of the wound was performed with negative pressure therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 35 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…First, the patient's skin and soft tissue are still developing and may not have the capacity to withstand the trauma of flap surgery. Second, the size of the defect in this case was extensive and involved a significant amount of tissue loss, making it difficult to harvest enough tissue for a flap [18]. Additionally, flap surgery carries a risk of complications such as flap necrosis, hematoma, and infection, which can be especially detrimental in young patients.…”
Section: Discussionmentioning
confidence: 96%
“…First, the patient's skin and soft tissue are still developing and may not have the capacity to withstand the trauma of flap surgery. Second, the size of the defect in this case was extensive and involved a significant amount of tissue loss, making it difficult to harvest enough tissue for a flap [18]. Additionally, flap surgery carries a risk of complications such as flap necrosis, hematoma, and infection, which can be especially detrimental in young patients.…”
Section: Discussionmentioning
confidence: 96%
“…2,3 In some situations, NPWT in combination with dermal substitutes and skin grafts could restore limb function, thus avoiding amputations. 4 High-energy traumas with open fractures are being increasingly treated with external fixation devices to achieve good stabilization, along with minimizing the risk of implant infections. However, the use of NPWT in association with external fixation may jeopardize the efficacy of the negative pressure treatment of the wound, increase treatment costs, or even discourage the physician from using this valuable treatment option.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study showed that VSD could bi‐directionally regulate HA metabolism, restoring its content to the level that was conducive for healing. Cigna found that when a posterior tibial injury wound was treated with HA and continuous negative pressure (−125 mmHg), the patient could walk independently 6 months later, and when supplemented with the appropriate physical therapy, the patient could have an early return to daily activities. Morykwas confirmed that granulation tissues grew fastest under the −125 mmHg pressure.…”
Section: Discussionmentioning
confidence: 99%